First pass effect in posterior circulation occlusions: Analysis from the CICAT registry. Issue 2 (February 2023) - Terceño, Mikel; Silva, Yolanda; Bashir, Saima; Chamorro, Ángel; Pérez de la Ossa, Natalia; Hernandez-Pérez, María; Castaño, Carlos; Camps-Renom, Pol; Wenger, Denisse; Cardona, Pere; Molina, Carlos; Rodríguez-Campello, Ana; et al.
Background: The first pass effect (FPE) is an independent predictor of functional independence in patients with large vessel occlusion in anterior circulation ischemic strokes. However, whether it predicts outcome in posterior circulation large vessel occlusion (PC-LVO) is uncertain. We aimed to study the frequency, characteristics, and predictors of FPE and its association with clinical outcomes in PC-LVO. Method: We performed an analysis from the prospective CICAT Registry. All patients with PC-LVO who underwent endovascular therapy between January 2016 and January 2020 were included. A centrally assessed clinical follow-up was performed at 3 months by blinded investigators. FPE was defined as the achievement of modified Thrombolysis In Cerebral Infarction 3 in a single pass of the endovascular thrombectomy device, and multi-pass effect (MPE) if it was achieved in more than one pass. A multivariable analysis was performed to identify whether FPE is an independent predictor of functional independence defined as a modified Rankin Score of 0–2. Results: We analyzed data from 265 patients in who FPE was achieved in 105 (39.6%). Patients with FPE were more likely to achieve functional independence compared to the non-FPE group (52.4% vs 25.1%, p < .001) and the MPE group (52.4% vs 26.7%, p < .001). FPE was independently associated with functional independence (adjusted odds ratio (aOR): 2.10, 95% confidence interval (CI) 1.01-4.37) but MPE was not (aOR: 0.92, 95% CI 0.40-2.13). Independent predictors of FPE were the use of direct aspiration, embolic mechanism of stroke, and the absence of general anesthesia (GA) use. Conclusions: FPE is an independent predictor of functional independence in PC-LVO and was associated with a significantly better outcome than MPE.